2009
DOI: 10.3233/cbm-2009-0617
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer susceptibility and genetic polymorphism of DNA repair gene XRCC4 in Taiwan

Abstract: Non-homologous end-joining (NHEJ) system is a major route in repairing double strand breaks (DSBs), and is important in maintaining the genome stability. The gene XRCC4 is a central role of the NHEJ system, and it is critical in carcinogenesis. In order to reveal the association between XRCC4 and lung cancer, we recruited 164 lung cancer patients and 649 healthy controls from central Taiwan, investigated seven novel polymorphic variants of XRCC4, includes C-1622T (rs7727691), G-1394T (rs6869366), G-652T (rs207… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 21 publications
2
36
3
1
Order By: Relevance
“…Jin et al [48] found that K589E polymorphism is associated with the risk of lung cancer in a Chinese population. Similar conclusion was obtained in the study of Taiwanese population, when it was found that the A allele of this polymorphism has a significant association and increase risk of lung cancer (P=0.0097) [35]. Interestingly, in other Taiwanese studies, in 2009, Wang et al [17], Tsai et al [44] & Bau et al [45] reported that the A allele EXO1 K589E conferred a significantly increased risk of gastric, oral and breast …”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Jin et al [48] found that K589E polymorphism is associated with the risk of lung cancer in a Chinese population. Similar conclusion was obtained in the study of Taiwanese population, when it was found that the A allele of this polymorphism has a significant association and increase risk of lung cancer (P=0.0097) [35]. Interestingly, in other Taiwanese studies, in 2009, Wang et al [17], Tsai et al [44] & Bau et al [45] reported that the A allele EXO1 K589E conferred a significantly increased risk of gastric, oral and breast …”
Section: Discussionsupporting
confidence: 76%
“…Regarding the important role of EXO1 in MMR system, this gene has become a famous target gene and widely investigated for its association with several cancers such as oral, CRC, lung and breast [17,35,37,44,47]. In this regard, numerous studies have reported several SNPs of EXO1 as genetic risk factors of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mul ple polymorphisms in the EXO1 gene have been described, in the noncoding regions as well as in exons of the gene. One polymorphism, EXO1 Glu589Lys (rs1047840) was found to be associated with suscep bility to lung cancer, breast cancer and gastric cancer in Asian popula ons [159][160][161][162]. The effect of the carriership of the Glu589Lys polymorphism may be modified by smoking status.…”
Section: Exo1 Genementioning
confidence: 99%